Pengaruh Keterampilan Komunikasi Mahasiswa terhadap Keberhasilan Melaksanakan Program Pejuang Muda Kementerian Sosial: - Devira Nur Astria; Chendi Liana (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study uses a quantitative approach with a simple linear regression analysis method. The theory used is the Communication Accommodation Theory from Howard Giles, which explains how and why a person adapts his communication behavior to the actions of others. The results of this study are (1) the average value of student communication skills is 65 with a percentage of 41% which is in the